Desenvolvimento de projeto orientativo para a instalação de um sistema fotovoltaico on-grid: estudo de caso de um sistema fotovoltaico residencial na cidade de Manaus. - Silva Junior, Leopoldino Lourenço Araújo da (Brasil, 2022)
Faced with the need for alternative sources for the energy matrix in Brazil. Photovoltaic solar energy presents itself as one of the most notable alternatives with regard to the cost of implementation and effective ecological protection because it is a renewable, clean source of energy and can be considered infinite. In this bias, it is presented in this work dimensioning techniques, understandings about economic viability and the installation of a Photovoltaic Solar System connected to the Electricity Grid of the City of Manaus - Am. This implementation is only possible due to the high solarimetric capacity existing in Brazil and the approval of normative resolutions nº 482/2014 and nº 687/2016 of ANEEL (National Electric Energy Agency), which includes the energy credit compensation system for mini-generation and micro-generation of solar energy, making it possible to install photovoltaic energy generating systems connected to the electrical grid. The case study made it possible to show that the installed project of photovoltaic systems is economically viable, despite the initial self-investment that is necessary for the acquisition of the technology, since it is possible to recover this investment much faster than expected, without the concern of the tariff increase, this fact is very clear in the case study presented as it shows the total recovery of the investment in less than 4 years, since it has a useful life of 25 years.